2010
DOI: 10.1097/tp.0b013e3181e228f7
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex Class 1 Chain-Related Antigen A Antibodies: Sensitizing Events and Impact on Renal Graft Outcomes

Abstract: In summary, (1) sensitizing events for MICA Abs are the same as for human leukocyte antigen Abs; (2) MICA Abs did not adversely affect renal graft outcomes in our cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 20 publications
1
47
0
1
Order By: Relevance
“…It has been suggested that pregnancy can induce MICA antibodies [20]. By contrast, the role of blood transfusions in the induction of MICA antibodies is unclear [23,29]. However, the effect of MICA mismatching in organ transplantation has not been fully addressed, largely because of a paucity of information on donor and recipient MICA types.…”
Section: Introductionmentioning
confidence: 88%
“…It has been suggested that pregnancy can induce MICA antibodies [20]. By contrast, the role of blood transfusions in the induction of MICA antibodies is unclear [23,29]. However, the effect of MICA mismatching in organ transplantation has not been fully addressed, largely because of a paucity of information on donor and recipient MICA types.…”
Section: Introductionmentioning
confidence: 88%
“…Identification of serum IgG MICA Abs was performed using Luminex beads bound to single recombinant MICA antigens (Gen-Probe Transplant Diagnostics), as described previously (14). HLA class I and II antibody screening was performed according to the manufacturer's instructions using Luminex beads coated with HLA class I and HLA class II antigens (Gen-Probe Transplant Diagnostics), providing either a positive or negative result.…”
Section: Anti-mica and Anti-hla Antibody Detectionmentioning
confidence: 99%
“…In solid organ recipients (8)(9)(10)(11) and dialysis patients (12), the overall rate of seroconversion to the seasonal flu vaccine is in the range of 30% to 50%. The use of adjuvanted vaccine has raised concerns for immunocompromised patients, because of possible induction of allo-immune responses, such as anti-human histocompatibility leukocyte antigen (HLA) antibodies (Abs) or MHC class I-related chain A (MICA) Abs (13)(14)(15)(16). Indeed, the AS03 adjuvant present in some vaccines promotes immunogenicity by modulating the expression of local cytokines and by increasing the antigen loading in monocytes (17).…”
Section: Introductionmentioning
confidence: 99%
“…8 Zou and associates 2 reported that antibodies against MICA alleles were detected in 217 of 1910 patients (11.4%) before transplant. The presence of MICA antibodies has been associated with renal allograft rejection.…”
Section: Discussionmentioning
confidence: 99%